Avaliação do Programa de Ação Integrada para o Aposentado – PAI: o caso do Projeto Integrado de Preparação para a Aposentadoria-PIPA - Dantas, Jaylson Gonçalves (2013)
This research aims at investigate whether the Assistance Program for the Elderly - PAI, by way of the Integrated Program of Retirement Preparation - PIPA, both sponsored by the Government of the State of Ceará, has the essence of caring and encourage the elderly for a pleasurable and productive activity in the retirement, with actions that are not merely ludic and often "infantilize" these people, through games and activities, even embarrassing. This research adopted as empirical group, 36 (thirty six) subjects participating in the said program, who made themselves ready, after a prior authorization, to participate. It was used as a methodology the application of a questionnaire consisting of open and closed questions, which analyzed data allowed us to outline the socioeconomic profile of the individuals involved, as well as realize the scope of the objectives proposed by the program. In general, participants are satisfied with the program and the activities offered, revealing that the research objectives were achieved, since the research came across itself with a large number of servers that are confident to face the ghost of the inactivity. However, as it is a public policy for the welfare of this population group, it is important to emphasize that public demand, because it is not static, requires periodic evaluations. In the specific case of PIPA, arises the need for this study to be done in another conjuncture, considering that the creation and reformulation of laws issued by the State allow that a reality, today, may be different tomorrow. Therefore, the participants of PIPA are servers that are approaching the end of the period of service and may be reinserted into the economy by social programs, especially in this time of crisis in which the world passes, Brazil and state of Ceará, where the neoliberalism is increasingly present and governments feel the need to avoid fiscal deficits.